What Policies Address Both the Coronavirus Crisis and the Climate Crisis? - Gustav Engström; Johan Gars; Niko Jaakkola; Therese Lindahl; Daniel Spiro; Arthur A. van Benthem (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The coronavirus pandemic has led many countries to initiate unprecedented economic recovery packages. Policymakers tackling the coronavirus crisis have also been encouraged to prioritize policies which help mitigate a second, looming crisis: climate change. We identify and analyze policies that combat both the coronavirus crisis and the climate crisis. We analyze both the long-run climate impacts from coronavirus-related economic recovery policies, and the impacts of long-run climate policies on economic recovery and public health post-recession. We base our analysis on data on emissions, employment and corona-related layoffs across sectors, and on previous research. We show that, among climate policies, labor-intensive green infrastructure projects, planting trees, and in particular pricing carbon coupled with reduced labor taxation boost economic recovery. Among coronavirus policies, aiding services sectors (leisure services such as restaurants and culture, or professional services such as technology), education and the healthcare sector appear most promising, being labor intensive yet low-emission—if such sectoral aid is conditioned on being directed towards employment and on low-carbon supply chains. Large-scale green infrastructure projects and green R&D investment, while good for the climate, are unlikely to generate enough employment to effectively alleviate the coronavirus crisis.
Keywords: Q54; E62; 330; coronavirus; climate policy